Sensory attributes of mineral fortified low fat buffalo milk Cheddar cheese - Perveen, Rashida; Sadiq, Masood; Sakandar, Hafiz Arbab (Progress in Nutrition, 2018)
Buffalo milk was fortified with different sources of calcium (Ca) and phosphorous (P) to manufacture of cheddar cheese. It was fortified with calcium chloride (CaCl2) and trisodium phosphate (Na3PO4) at level of 10 (T1), 20 (T2) and 30 (T3) mM/ milk. All samples of cheddar cheese (0, 15 and 30 days) were analyzed for moisture, fat, mineral profile such as calcium, sodium, phosphorous and potassium, sensory analysis (hand firmness, chew down degree of breakdown and chew down smoothness). The fat content of Ca and P enriched cheeses exhibited significant differences due to treatments (23.87±0.63to 23.13±0.56%). No obvious significantly effects were observed in moisture fat, mineral profile, ash and organoleptic characteristics on cheddar cheeses during ripening. The salt fortified cheese showed significant effect of mineral with treatments; sodium (612.52±4.17 to 634.47±7.68 mg/100g), potassium (64.76±2.21 to 74.04±2.02mg/100g), calcium (831.58±4.55 to 874.45±2.62mg/100g). Additionally, hedonic response of developed cheeses was significantly affected due to treatments. Decisively, colloidal supramolecular structures of caseins in buffalo milk play a pivotal role in cheese making and other related organoleptic characteristics. Thus, buffalo milk casein along with calcium and phosphorus incorporation for the development of novel cheese formulation is a pragmatic approach in the field of dairy technology.